Multiple Symptoms Study 3 – An extended-role general practitioner clinic for patients with persistent physical symptoms: a Randomised Controlled Trial - Christopher Burton; Cara Mooney; Laura Sutton; David White; Jeremy Dawson; Kate Fryer; Monica Greco; Michelle Horspool; Aileen Neilson; Gillian Rowlands; Tom Sanders; Ruth Thomas; et al. (Health and Social Care Delivery Research)
Background People with multiple and persistent physical symptoms have impaired quality of life and poor experiences of health care. We aimed to evaluate the effectiveness of a community-based Symptoms Clinic intervention in people with multiple and persistent physical symptoms. Trial design Pragmatic multicentre individually randomised parallel group clinical trial. Methods Participants: Recruitment was between December 2018 and December 2021 in four areas of the UK. Eligibility was based on electronic health records, healthcare use and multiple physical symptoms (PHQ-15 between 10 and 20) which were not due to other medical conditions. Intervention delivery changed from face to face to online in 2020 in response to the pandemic. Interventions: Participants were randomised to receive the Symptoms Clinic plus usual care (intervention) or usual care alone (control). The Symptoms Clinic is a short-term extended medical consultation-based intervention delivered over approximately 8 weeks. Objective: To test the clinical and cost-effectiveness of an extended-role general practitioner ‘Symptoms Clinic’ for people with persistent physical symptoms. Outcome: The primary outcome measure was the PHQ-15 at 52 weeks post randomisation. Randomisation: Participants were randomised 1 : 1 using a centralised web-based system, stratified by study centre with random permuted blocks of varying sizes. Masking: It was not possible to mask participants to their allocation. Outcome assessors who handled patient-reported questionnaires were masked to allocation. Results Numbers randomised: 354 participants were randomised into the trial: 176 to the usual care group and 178 to the intervention group. Numbers analysed: 132 participants in the usual care group and 144 participants in the intervention group were included in the analysis representing 77.8% retention. Outcome: Mean (SD) PHQ-15 at baseline was 14.9 (3.0) in the control group and 15.0 (2.9) in the intervention group. At 52 weeks it was 14.1 (3.7) in the control group and 12.2 (4.5) in the intervention group. The between-group difference, adjusted for age, sex, baseline PHQ-15 and clinician effect was −1.82 (95% CI −2.67 to −0.97; p < 0.001) favouring the intervention. Harms: There were no significant between-group differences in the proportions of patients experiencing non-serious (−0.03, 95% CI −0.11 to 0.05) or serious (0.02, 95% CI −0.02 to 0.07) adverse events. All serious adverse events were deemed unrelated to trial interventions. Economic evaluation: Cost-effectiveness analysis indicated an incremental cost-effectiveness ratio of £15,751/QALY. Process evaluation: The intervention was delivered with high fidelity and was acceptable to patients. The intervention appeared to act through the hypothesised mechanism of explanation as a bridge from uncertainty about the cause to actions to manage symptoms. Limitations and further research: The intervention was delivered by a small number of GPs in long consultations. Further research should examine wider implementation and how to integrate elements of the intervention into shorter consultations. Conclusions The Symptoms Clinic delivered by specially trained GPs leads to a clinically meaningful improvement in physical symptoms at 52 weeks and is likely to be a cost-effective addition to current care. Funding This synopsis presents independent research funded by the National Institute for Health and Care Research (NIHR) Health and Social Care Delivery Research programme as award number 15/136/07. Plain language summary Why did we do this study? One in fifty UK adults regularly has multiple symptoms which make life difficult for them. These persistent physical symptoms include pain, fatigue, dizziness, stomach problems and many others. Because medical tests don’t show a cause for persistent physical symptoms, doctors often don’t know how to help and patients can feel no-one believes them. We developed a way of using new scientific knowledge about symptoms to help people make sense of their own symptoms and to try new things to help. We tested this in a Symptoms Clinic. We wanted to know if patients found a difference 1 year later. What did we do? Three hundred and fifty-four people with multiple symptoms joined the study between December 2018 and December 2021. Half of them had up to four appointments with a specially trained GP at the Symptoms Clinic, while the others got their usual care. We asked people in both groups about their symptoms after 3, 6 and 12 months and compared the two groups. We also listened to what happened in the clinic and interviewed some people to find out what it was like. What did we find? People who attended the Symptoms Clinic found it gave them better ways to understand and manage their symptoms. A year after they joined the study, people who had attended the Symptoms Clinic had less symptoms bothering them than those who hadn’t. They also had a better quality of life. This was even though their last Symptoms Clinic appointment was 9 months ago. What does this mean for people with persistent physical symptoms? Explaining physical symptoms in this way can make a real difference for patients. This research shows us how health professionals can do it well and the difference it can make.